Identification and Optimization of 4‐Anilinoquinolines as Inhibitors of Cyclin G Associated Kinase. (27th November 2017) - Asquith, Christopher R. M.; Laitinen, Tuomo; Bennett, James M.; Godoi, Paulo H.; East, Michael P.; Tizzard, Graham J.; Graves, Lee M.; Johnson, Gary L.; Dornsife, Ronna E.; Wells, Carrow I.; Elkins, Jonathan M.; Willson, Timothy M.; et al.
Abstract: 4‐Anilinoquinolines were identified as potent and narrow‐spectrum inhibitors of the cyclin G associated kinase (GAK), an important regulator of viral and bacterial entry into host cells. Optimization of the 4‐anilino group and the 6, 7‐quinoline substituents produced GAK inhibitors with nanomolar activity, over 50 000‐fold selectivity relative to other members of the numb‐associated kinase (NAK) subfamily, and a compound (6, 7‐dimethoxy‐ N ‐(3, 4, 5‐trimethoxyphenyl)quinolin‐4‐amine;49 ) with a narrow‐spectrum kinome profile. These compounds may be useful tools to explore the therapeutic potential of GAK in prevention of a broad range of infectious and systemic diseases. Abstract : Targeting GAK : The availability of chemical probes with improved selectivity for cyclin G associated kinase (GAK) or a different spectrum of off‐targets would be useful in target validation studies. Herein we report the synthesis and characterization of 4‐anilinoquinolines and 4‐anilinoquinazolines as potent narrow‐spectrum GAK inhibitors. Several of these compounds have the potential for development into high‐quality chemical probes for the study of GAK biology.